2021
DOI: 10.3390/app11094167
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Criteria Optimization of an Innovative Suspension System for Race Cars

Abstract: The purpose of the present work was to design, optimize, and test an innovative suspension system for race cars. The study was based on a comprehensive approach that involved conceptual design, modeling, simulation and optimization, and development and testing of the experimental model of the proposed suspension system. The optimization process was approached through multi-objective optimal design techniques, based on design of experiments (DOE) investigation strategies and regression models. At the same time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Steering linkage of a bus is optimized using RSM approach [9]. Multi-criteria optimization of a suspension system is realized utilizing the conventional regression models [10]. DOE approach is used for a solid axle of a heavy commercial vehicle on optimizing steering kinematics which used statistical analysis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Steering linkage of a bus is optimized using RSM approach [9]. Multi-criteria optimization of a suspension system is realized utilizing the conventional regression models [10]. DOE approach is used for a solid axle of a heavy commercial vehicle on optimizing steering kinematics which used statistical analysis [11].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the improved algorithm outperformed the traditional multi-objective particle swarm algorithm and the genetic algorithm. Totu and Alexandru [21] presented a comprehensive design method based on the least squares approach for the optimal design of an innovative racing car suspension system. This study used Adams/View and Adams/Insight to build a regression model and carry out the optimization design.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, to simplify the theoretical models, the bushings are modeled by spherical (ball) joints, thus neglecting the linear deformations (which are, however, very small compared to the angular ones) [2][3][4][5][6][7]. In the case of the triangular guidance bars, with double articulation to the chassis and/or wheel carrier, as the case may be, the two afferent spherical connections determine, in fact, a revolute joint.…”
Section: Introductionmentioning
confidence: 99%